Business, bankruptcy, and beliefs: The financial demise of NBA stars - Ruby Henry (Institute for the Study of Labor (IZA), 2013)
The financial troubles of professional athletes are an ongoing topic of intrigue. In general, the zealousness brought to private equity schemes are a common factor in observed financial insolvency. Considering the behavioral attribute of self-confidence I propose a simple model which explains entrepreneurial activity and adverse financial outcomes. The model implies that investment effort increases with self-confidence, while promoting financial solvency. Constructing a unique database of NBA players affords a singular opportunity to measure confidence directly from behavior, avoiding bias from self-reported surveys. In addition, I observe for-profit business ventures and use this data to test the model's implications for the outcomes of both entrepreneurial activity (investment effort) and bankruptcy. Without correcting for endogeneity it does appear that starting businesses causes bankruptcy. After using charitable foundations as an instrument, however, the data confirms the model's prediction - that investment effort is associated with financial solvency. That said, I also find that the effect of confidence on bankruptcy to be non-monotonic. Having some confidence decreases the probability of bankruptcy, but high levels increase this probability.
Keywords: D10; I20; J13; 330; self-confidence; bankruptcy; athletes; entrepreneurs influence; entrepreneurship